Spiritual Emotional Freedom Technique on Reducing The Symptoms of Patients at Risk of Violent Behavior in The Work Area UPTD Puskesmas Karangrejo in 2024 - Saleh; Agustriyani, Feri (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: The purpose of this study was to apply the spiritual emotional freedom technique to reduce the symptoms of patients at risk of violent behavior in the UPTD Puskesmas Karangrejo Work Area. Method: Data collection methods using mental nursing care assessment sheets and SEFT SOP sheets. The study used two mental patients with the problem of risk of violent behavior. Result: The results of nursing care obtained the results of evaluations that researchers conducted on clients based on the criteria that researchers compiled on the diagnosis of risk of violent behavior resolved on day 3 of the implementation of nursing care by providing SEFT to two patients, where both patients did not show signs of violent behavior and both patients were able to apply spiritual emotional freedom technique 5 times within one day. Conclusion: Suggestions for patients and families can apply the position of spiritual emotional freedom technique when to reduce signs of violent behavior and as an alternative in reducing the impact of patients who experience the risk of violent behavior in mental patients.